Development of an Agricultural Primary Productivity Decision Support Model: A Case Study in France - Sandén, Taru; Trajanov, Aneta; Spiegel, Heide; Kuzmanovski, Vladimir; Saby, Nicolas P. A.; Picaud, Calypso; Henriksen, Christian Bugge; Debeljak, Marko (Frontiers in Environmental Science, 2019)
Agricultural soils provide society with several functions, one of which is primary productivity. This function is defined as the capacity of a soil to supply nutrients and water and to produce plant biomass for human use, providing food, feed, fiber and fuel. Up to about one quarter of all agricultural soils are degraded. This is responsible for an ongoing decrease in biomass productivity. For farmers, the productivity function delivers an economic basis and is a prerequisite for agricultural sustainability. Our study was designed to develop an agricultural primary productivity decision support model. To obtain a highly accurate decision support model that helps farmers and advisors to assess and manage the provision of the primary productivity soil function on their agricultural fields, we addressed the following specific objectives: i) to construct a qualitative decision support model to assess the primary productivity soil function at the agricultural field level; ii) to carry out verification, calibration and sensitivity analysis of this model, and iii) to validate the model based on empirical data. The result is a hierarchical qualitative model comprising of 25 input attributes describing soil properties, environmental conditions, cropping specifications and management practices on each respective field. An extensive dataset from France containing data from 399 sites was used to calibrate and validate the model. The large amount of data enabled data mining to support model calibration. The accuracy of the decision support model prior to calibration supported by data mining was ~ 40%. The data mining approach improved accuracy to 77%. The proposed methodology of combining decision modelling and data mining proved to be an important step forward. This iterative approach yielded an accurate, reliable and useful decision support model for the assessment of the primary productivity soil function at the field level. This can assist farmers and advisors in selecting the most appropriate crop management practices. Embedding this decision support model in a set of complementary models for four adjacent soil functions, as endeavored in the H2020 LANDMARK project, will help take the integrated sustainability of arable cropping systems to a new level.